From Perahus to Cars: Sectoral Planning and the Transformation of Fishing Villages in Kuching, Sarawak - Azmah, Arzmi (2024)
As Kuching, Sarawak expanded in the 20th century, Malay fishing villages on the edge of Kuching’s rivers faced challenges due to congested waters and disruptions caused by sectoral planning policies. The villages’ growth trajectories were determined by economic activities in their vicinity, such as industrial estates, trading ports, educational institutions, or eco- tour-ism in rainforest parks. Situated in various locations, they have undergone significant changes that are directly linked to the expansion of Kuching and the emergence of new infrastructure. The replacement of rivers with roads has gradually severed their historic connection to the river, leading to a fundamental reshaping of their built environment, livelihoods, and sense of community. This study examines the transformation of four Kuching fishing villages from the 20th century to the present day. Drawing on in-depth semi- structured interviews with villagers, preliminary fieldwork, studies of settlement morphology, and analysis of planning documents, this research uncovers the often- overlooked human costs of sectoral planning and offers valuable lessons for planners facing similar challenges in Southeast Asia and be-yond. Through the lens of four fishing villages in Kuching, we reveal the complex interplay between infrastructure growth, social resilience, and economic viability in the face of rapid development and call for a nuanced approach to planning that prioritises the well-being of peripheral rural communities.